Rancang Bangun Aplikasi Rental Kostum Cosplay Dnrei Berbasis Web Menggunakan Framework Codeigniter - Annastia Reza Dzulhaj; Didi Juardi; Asep Jamaludin (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
The cosplay costume rental industry in Indonesia faces significant operational challenges due to its reliance on manual methods via WhatsApp and Instagram. Dnrei Cosplay Costume Rental, which has been operating since 2019, experiences problems including slow order responses, inaccurate stock information, and inefficient transaction recording. This study aims to design and build a web-based application to address these issues using the CodeIgniter framework with the System Development Life Cycle (SDLC) Prototype methodology. The system integrates features for real-time costume availability checking, online ordering, an interactive rental schedule calendar, admin inventory management, and digital payment through the Midtrans payment gateway with a MySQL database. Testing was conducted through Black Box Testing and User Acceptance Testing (UAT) involving ten respondents. Black Box Testing results confirmed that all system functionalities performed as expected, while UAT produced an average satisfaction score of 91.6%. Comparative evaluation demonstrated that system implementation successfully reduced costume availability checking time from 10—15 minutes to less than one minute. This system is proven to measurably improve operational efficiency and overall customer experience at Dnrei Cosplay Costume Rental.